ANALISIS TENTANG PERANAN BADAN PERMUSYAWARATAN NAGARI GALUGUA KECAMATAN KAPUR IX KABUPATEN LIMAPULUH KOTA - Oki Ardika Putra; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract : This research was conducted as motivated by yet progressed to the fullest role Nagari Galugua Consultative Body. In this case as an important instrument Nagari role Consultative Body which duties and functions as a legislative body villages as stipulated in the legislation. Formulation of the problem in this research is how the role of consultative bodies Nagari Galugua District of Kota Kapur IX Limapuluh? and this study aims to determine the role of consultative bodies Nagari Galugua Limapuluh District of Kota Kapur IX. As for the population in this study is villagers' Galugua 1,227 people, while the sample in this study is the caretaker Consultative Body Nagari of 7 people, the government nagari as many as 10 people and society in this case public figures as many as 25 people and the general public as much as 80 people. A sampling technique that uses purposive sampling technique.Data was collected through observation, questionnaires and interviews. In analyzing the data using a combination of methods (Mixed Methods). These results indicate that the role of consultative bodies Nagari Galugua District of Kapur IX Limapuluh based benchmarks by Husaini Usman and Purnomo Setiady Akbar (2011: 146) is the number who answered